(untitled) (University Journal of Zoology, Rajshahi University, 2007)
Key words: Mulberry; biochemical changes; cocoon characters; leaf spot disease; Cercospora moricola Univ. j. zool. Rajshahi Univ. Vol.21, 2002. pp. 85-87